A MODEL FOR OXYGEN AND SULFUR ISOTOPE FRACTIONATION IN SULFATE DURING BACTERIAL SULFATE REDUCTION PROCESSES - Brunner B.; Bernasconi S.M.; Kleikemper J.; Schroth M.H. (My University, 2005)
We present a model of bacterial sulfate reduction that includes equations describing the fractionation relationship between the sulfur and the oxygen isotope composition of residual sulfate (δ34SSO4_residual, δ18OSO4_residual) and the amount of residual sulfate. The model is based exclusively on oxygen isotope exchange between cell-internal sulfur compounds and ambient water as the dominating mechanism controlling oxygen isotope fractionation processes. We show that our model explains δ34SSO4_residual vs. δ18OSO4_residual patterns observed from natural environments and from laboratory experiments, whereas other models, favoring kinetic isotope fractionation processes as dominant process, fail to explain many (but not all) observed δ34SSO4_residual vs. δ18OSO4_residual patterns. Moreover, we show that a “typical” δ34SSO4_residual vs. δ18OSO4_residual slope does not exist. We postulate that measurements of δ34SSO4_residual and δ18OSO4_residual can be used as a tool to determine cell-specific sulfate reduction rates, oxygen isotope exchange rates, and equilibrium oxygen isotope exchange factors. Data from culture experiments are used to determine the range of sulfur isotope fractionation factors in which a simplified set of equations can be used. Numerical examples demonstrate the application of the equations. We postulate that, during denitrification, the oxygen isotope effects in residual nitrate are also the result of oxygen isotope exchange with ambient water. Consequently, the equations for the relationship between δ34SSO4_residual, δ18OSO4_residual, and the amount of residual sulfate could be modified and used to calculate the fractionation-relationship between δ15NNO3_residual, δ18ONO3_residual, and the amount of residual nitrate during denitrification.